CONTENT AND STRUCTURE OF INCLUSIVE COMPETENCE - Abdubannobova Mahliyo Abdurashid qizi (Web of Journals Publishing, 2025)
This article describes the content of inclusive competence and the components of inclusive competence - motivational, cognitive, reflective and basic operational competences.
Keywords: Motivational component, inclusive competence, cognitive component, reflective component, reflective competence, operational component.